Challenges for bilingual legal education: Evidence from a Malaysian Law Faculty - Powell, R.; Chew, L.H. (2015)
Several common law jurisdictions (e.g. Bangladesh, Hong Kong) and some civil law systems (Macao, Timor Leste) function in two or more languages as a result of retaining laws and legal networks that evolved in a colonial medium while attempting to enhance legal transparency or conform to national language policies by recognizing local languages of wider communication. Unlike systems that mediate language difference through interpreting and translation, bilingual systems place a particular linguistic onus on lawyers, many of whom have to switch languages when switching communication sites (superior court, subordinate court, office etc.), communicative tasks (drafting litigation, commercial documents or submissions), or interlocutors (judges, witnesses, clients). It might be expected that bilingual teaching and the provision of bilingual resources at law school would be indispensable to raising proficiently bilingual lawyers. Yet comprehensive bilingual legal education appears unusual.